Functional MICA Variants Are Differentially Associated with Immune-Mediated Inflammatory Diseases - Wang, Chin-Man; Tan, Keng-Poo; Wu, Yeong-Jian Jan; Zheng, Jian-Wen; Wu, Jianming; Chen, Ji-Yih (International journal of molecular sciences, 2024)
As the principal ligand for NKG2D, MICA elicits the recruitment of subsets of T cells and NK cells in innate immunity. MICA gene variants greatly impact the functionality and expression of MICA in humans. The current study evaluated whether MICA polymorphisms distinctively influence the pathogenesis of psoriasis (PSO), rheumatoid arthritis (RA), and systemic lupus erythematosus (SLE) in Taiwanese subjects. The distributions of MICA alleles and levels of serum soluble NKG2D were compared between healthy controls and patients with PSO, RA, and SLE, respectively. The binding capacities and cell surface densities of MICA alleles were assessed by utilizing stable cell lines expressing four prominent Taiwanese MICA alleles. Our data revealed that MICA*010 was significantly associated with risks for PSO and RA (PFDR = 1.93 × 10−15 and 0.00112, respectively), while MICA*045 was significantly associated with predisposition to SLE (PFDR = 0.0002). On the other hand, MICA*002 was associated with protection against RA development (PFDR = 4.16 × 10−6), while MICA*009 was associated with a low risk for PSO (PFDR = 0.0058). MICA*002 exhibited the highest binding affinity for NKG2D compared to the other MICA alleles. Serum concentrations of soluble MICA were significantly elevated in SLE patients compared to healthy controls (p = 0.01). The lack of cell surface expression of the MICA*010 was caused by its entrapment in the endoplasmic reticulum. As a prevalent risk factor for PSO and RA, MICA*010 is deficient in cell surface expression and is unable to interact with NKG2D. Our study suggests that MICA alleles distinctively contribute to the pathogenesis of PSO, RA, and SLE in Taiwanese people.